Role of herbal hair oil in the management of hair loss - Anpuchelvi, S.; Sritharan, G. (University of Kelaniya, 2012)
Hair has no vital function in humans, yet its psychological function are extremely important. It imparts a youthful and attractive look to both males and females. Hair growth in each hair follicle occurs in a cycle. There are three main phases of the hair growth cycle; anagen (growth), catagen (involution) and telogen (rest). In general, 50-100 hairs are shed everyday. More common causes of hair loss are Genetic disease and abnormal level of hormone production. Which may be associated with Hypopituitarism, thyroid gland defects and Cushing's syndrome. Consumption of low fatty acids and vitamin C in the diet may lead to anagen effluvium. The cancer treatments such as chemotherapy, Ionizing radiation, X rays and gamma rays. Toxic agents such as Thallium, arsenic, lead, bismuth, vitamin A and derivative toxic drugs. Management of hair fall is extremely complex. The formula of hair oil in this study is taken from old manuscript. Herbal Hair oil is a poly herbal formulation from Alternanthera sessile, Lawsonia inermis, Murraya koenigii, Costus speciosus, Santalum album, Curcuma zeodaria, Mollugo cerviana, Elettaria cardamomu and coconut oil. The purpose of this study is to evaluate the safety and efficacy of Herbal hair oil in hair loss. This clinical trial was conducted at outpatient department of Herbal Health Care Centre, Kokuvil, Jaffna. Number of patients involved in this study is hundred. There were both sexes in the age group of 18-35 years selected who were suffering from hair loss. Informed written consents were obtained from willing patients. Patients on immunosuppressive drugs and applying other topical therapy for hair loss were excluded from this study. Infection and infestation of scalp, dandruff, stress level, dietary habits, previous illnesses and treatment details were obtained from history taking and clinical examination. All the enrolled patients underwent a clinical examination for hair loss. The patients were advised to give gentle massage to the scalp covering whole area with hair oil and rinse it in the morning. The response to therapy was evaluated at intervals of four weeks covering 16 weeks. The criteria to evaluate this study were formulated as level of hair falling, itchiness level, and dryness level of scalp. Response was evaluated on an analogue scale of 0-3 (0-being Nil, 1-being Moderate, 2-being Good, 3-being Excellent). The mean hair fall at entry was 121.3 +/- 7.2 which significantly (p<0.05) improved with continued treatment at 16th week. Itching was present in 42 cases at entry, reduced significantly (p<0.05) at the end. 2 cases reported excellent response, 42 cases reported good response, 22 cases reported moderate response, 10 cases reported poor response, 2 cases reported no response. No adverse reaction reported in this study period. This clinical study clearly demonstrates the beneficial effects of hair oil in the treatment of hair loss.
Keywords: Herbal hair oil; Polyherbal